Alan Mikhail, Under Osman’s Tree: The Ottoman Empire, Egypt, and Environmental History - Dedeoglu, Cagdas (Journal for the Study of Religion, Nature and Culture, 2018)
Alan Mikhail, Under Osman’s Tree: The Ottoman Empire, Egypt, and Environmental History (Chicago and London: The University of Chicago Press, 2017), 336 pp., 45.00 (pbk), ISBN: 978-0-226-42717-1.